Micro, Small, Medium Enterprises (MSMEs) Development Strategy Based on Omnibus Law - Purborini, Vivi Sylvia; Sinda Eria Ayuni (International Journal of Technology and Education Research, 2024)
MSMEs as the strongest business sector compared to other sectors are also the largest contributors to Indonesia's economic growth. MSMEs are business innovations that can be used as important pillars for Indonesia as a developing country, with the increase in entrepreneurs it can improve the welfare of the Indonesian people. The position of MSMEs in the national economy has an important and strategic role. This condition is very possible because the existence of MSMEs is quite dominant in the Indonesian economy, with the reason for the large number of industries and in every economic sector, the great potential in absorbing labor, and the contribution of MSMEs in the formation of Gross Domestic Product (GDP) is very dominant. The research method used by the author is the doctrinal legal research method or normative law, namely research that uses legislation, legal rules, and norms as sources of law related to the problems to be studied. The development of MSMEs is one of the government's efforts as the ruler of the country to increase investment and open up employment opportunities. The Indonesian House of Representatives' critical thinking in discussing the Job Creation Law will determine the direction of the policy for the ease, empowerment, and protection of MSMEs